2021
DOI: 10.3390/min11111169
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Fluorescence and Laser-Induced Breakdown Spectroscopy Analysis of Li-Rich Minerals in Veins from Argemela Tin Mine, Central Portugal

Abstract: In this work, X-ray fluorescence (XRF) and Laser-induced breakdown spectroscopy (LIBS) analyses were applied to samples of quartz, montebrasite, and turquoise hydrothermal veins in the Argemela Tin Mine (Central Portugal). Montebrasite (LiAl(PO4)(OH,F)) is potentially the main ore mineral; with its alteration, lithium (Li) can disseminate into other minerals. A hand sample was cut and analyzed by XRF and LIBS for several elements of interest including Cu, P, Al, Si, and Li. Although XRF cannot measure Li, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Riberio et al [62] used a portable XRF analyzer and a bespoke laboratory LIBS system to examine the same locations on quartz, montebrasite, and turquoise in a slab cut from a hydrothermal vein at the Argemela Tin Mine in Central Portugal. LIBS results demonstrated that montebrasite can be distinguished from turquoise because the turquoise did not contain Li.…”
Section: Laboratory Libs Analysis Of LI In Geological Materialsmentioning
confidence: 99%
“…Riberio et al [62] used a portable XRF analyzer and a bespoke laboratory LIBS system to examine the same locations on quartz, montebrasite, and turquoise in a slab cut from a hydrothermal vein at the Argemela Tin Mine in Central Portugal. LIBS results demonstrated that montebrasite can be distinguished from turquoise because the turquoise did not contain Li.…”
Section: Laboratory Libs Analysis Of LI In Geological Materialsmentioning
confidence: 99%
“…Constraints, such as the influence of water content on measurements, the necessity to handle sample volumes, and the requirement for sample preparation pellets, have been noted in prior studies, as identified by Senesi, Cabral, Menegatti, Marangoni and Nicolodelli [12]. Furthermore, the challenges have been acknowledged in quantifying the elements within dried tissues, along with considerations regarding the influence of nitrogen in the atmosphere [23,24]. These challenges posed barriers to the implementation of LIBS in viticultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, accurate measurement of Mn content is important in the analysis of low alloy steel. As an emission spectroscopy technology, laser-induced breakdown spectroscopy (LIBS) has many advantages, such as fast analysis, high sensitivity and online real-time monitoring, compared with the traditional technologies such as flame atomic absorption spectrometry and X-radial fluorescence [2][3][4][5]. The main function of LIBS is to analyze the composition and content of elements in substances.…”
Section: Introductionmentioning
confidence: 99%